DEVELOPING ENGLISH LESSON PLAN AND STUDENTS’ WORKSHEET BASED ON DISCOVERY LEARNING IN TEACHING DESCRIPTIVE TEXT FOR THE FIRST YEAR STUDENTS OF SMP - Hamidina Fadhliani; Atni Prawati; Mahdum Mahdum (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This research is aimed to develop English learning documents (lesson plan and students’ worksheet) based on discovery learning as one of learning models suggested in the 2013 Curriculum and to find out the validity level of developing English learning documents based on discovery learning in teaching descriptive text for the first year students of SMP. The research design is Research & Development (R&D) applied 4D model by Thiagarajan (1974). To develop English learning documents, there were three stages involve in this research, (a) define stage that is done to set and define the product development requirements, (b) design stage that is done to plan the draft of learning documents and arranged it into the format and (c) develop stage that is done to modify and validate the learning documents. In order to find out the validity level of developing English learning documents, the data were collected using validation sheet of lesson plan and validation sheet of students’ worksheet validated by experts. Based on data analysis result, the validation score of lesson plan is 90.91% and the validation score of students’ worksheet is 89.37%. The result showed that the learning documents in the form of lesson plan and students’ worksheet were very valid and can be implemented in a classroom.Key words: Research and Development (R&D), Lesson plan (LP), Students’ Worksheet (SW),Discovery Learning, Descriptive Text.